The Effect of Therapeutic Ultrasound on Metallic Implants: A Study in Rats - (:unkn) unknown (W B SAUNDERS CO-ELSEVIER INC, 2011)
Objective: To investigate whether therapeutic ultrasound (US) use over metallic implants has the potential for adverse effects as a result of greater temperature increases at the tissue-metal interface. Design: A randomized controlled trial. Setting: A research laboratory. Animals: Sprague-Dawley rats (N=40; weight, 230-300g) were used and divided into 3 study groups. Interventions: In group 1, both limbs of 10 rats were used for evaluation of temperature changes. Metal pins were placed into the femur of the left limb, and the right limbs were used as controls. A thermal sensor was placed into the medulla to record the elevation of tissue temperature during US application. In groups 2 and 3 with 15 rats in each, a midshaft femoral fracture was produced, and intramedullary fixation was performed with metal pins. Group 2 received US treatment for 5 minutes daily and continued for 27 days. Group 3 served as controls. Main Outcome Measures: The rats in groups 2 and 3 were killed on postoperative day 30. The specimens were evaluated by radiology, histopathology, and biomechanics. Results: The presence of metal in bone did not cause an increased temperature rise. US application did not increase or decrease callus formation, and there was no tissue necrosis. The average removal torques of pins in groups did not show a significant difference. Conclusions: Internal fixation with metallic implants may not be a contraindication for therapeutic US treatment.
Keywords: Bone Fracture healing, implant failure, metal; Heating; Loosening; Metallic implant; Rehabilitation; Ultrasound